The Cambridge companion to legal positivism - Spaak, Torben; Mindus, Patricia (Cambridge companions to law, 2021)
Legal positivism is one of the fundamental theories of jurisprudence studied in law and related fields around the world. This volume addresses how legal positivism is perceived and makes the case for why it is relevant for contemporary legal theory. The Cambridge Companion to Legal Positivism offers thirty-three chapters from leading scholars that provide a comprehensive commentary on the fundamental ideas of legal positivism, its history and major theorists, its connection to normativity and values, its current development and influence, as well as on the criticisms moved against it.